ON $\alpha$-ABSORBING SUBMODULES - T. Khumprapussorn (My University, 2020)
Let R be a commutative ring with identity.For an R-module M , the notion of α-absorbing submodules and weakly α-absorbing submodules are defined.We study some basic properties of α-absorbing submodules and weakly α-absorbing submodules.Also, we give some characterizations of them.
Keywords: Alpha (finance); Fuzzy and Soft Set Theory